2015
DOI: 10.1007/s11869-015-0367-y
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of bacterial species compositions in sand dunes and dust aerosol in an Asian dust source area, the Taklimakan Desert

Abstract: Airborne microorganisms (bioaerosol) from the China desert region, which are released into the atmosphere, disperse by the Asian dust event and affect ecosystems, human life, and atmospheric processes in downwind areas. However, the dynamics of airborne bacteria over the China desert regions have rarely been investigated. In this study, we analyzed bacterial communities in aerosols of the Asian dust source region (Taklimakan Desert) and compared them with the bacterial communities in sand dunes, in order to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 47 publications
1
19
0
3
Order By: Relevance
“…Previous research has also reported marine bacterial transported by Asian dust (Maki et al, ) and African dust (Polymenakou et al, ) events. Members of Actinobacteria , which are frequently dominated in desert bacterial communities (An et al, ; Puspitasari et al, ) and in anthropogenic pollutants (Cao et al, ), tended to increase during dust events with anthropogenic pollutants in the both sites. The dust events came on the way of northern continental China (close to Siberia mountain areas) which avoided passing through industrial zones, would carry phyllospheric bacteria, such as Proteobacteria, and increase their abundances in atmosphere instead of Actinobacteria .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has also reported marine bacterial transported by Asian dust (Maki et al, ) and African dust (Polymenakou et al, ) events. Members of Actinobacteria , which are frequently dominated in desert bacterial communities (An et al, ; Puspitasari et al, ) and in anthropogenic pollutants (Cao et al, ), tended to increase during dust events with anthropogenic pollutants in the both sites. The dust events came on the way of northern continental China (close to Siberia mountain areas) which avoided passing through industrial zones, would carry phyllospheric bacteria, such as Proteobacteria, and increase their abundances in atmosphere instead of Actinobacteria .…”
Section: Resultsmentioning
confidence: 99%
“…These bacteria were typically dominant populations associated with mineral dust particles and frequently detected from Asian‐dust aerosol samples collected at high altitudes above Asian desert (Dunhuang: Maki et al, ) and downwind areas (Korea: Cha et al, ; Jeon et al, , Japan: Maki, Hara, et al, ; Yamaguchi et al, ). The Bacilli lineage of phylum Firmicutes are generally found in terrestrial environments in the Gobi and Taklimakan Deserts (Puspitasari et al, ) and their ability to form endospores can help maintain viabilities against atmospheric stressors (Nicholson et al, ). Members of the Cytophagaceae lineage are often attach onto the organic aggregates (Newton et al, ), suggesting that the biofilm formation on organic aggregates can protect bacterial cells in atmosphere.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Actinobacteria sequences appeared in the samples collected from air masses that were transported throughout the Korean Peninsula on 19 March 2013, 28 April 2013, and 20 March 2015. Actinobacteria members are frequently dominant in terrestrial environments but seldom survive in the atmosphere for a long time, because they cannot form spores (Puspitasari et al, 2015). However, the family Micrococcaceae in Actinobacteria was primarily detected from anthropogenic particles collected in Beijing, China (Cao et al, 2014).…”
Section: Dominant Bacterial Populations In the Air Masses Transportedmentioning
confidence: 99%
“…Besides, human activities like walking and running disturb the settled dust particles making them re-circulate in the atmosphere [12]. Previous studies have identified that Pseudomonas, Bacillus and Acinetobacter species are associated with dust particles [33]. In addition, the presence of an attached washroom could be another reason.…”
Section: Percentage Of Childrenmentioning
confidence: 99%